A case of acute appendicitis due to intestinal schistosomiasis. (January 2019) - Salih, Mugahid A.
Abstract: Introduction: Intestinal Schistosomiasis is a parasitic disease caused by Schistosoma mansoni or Schistosoma japonica. Sudan is considered one of the endemic areas of schistosomiasis and many studies were done as regard to the prevalence and impact of the disease. Schistosomal appendicitis is rare, particularly in developed countries compared to endemic areas. Case report: This is a case of 36 –year- old man with past history of schistosomiasis presented with features of intestinal obstruction to Ibrahim Malik teaching hospital in Khartoum-Sudan. Exploratory laparotomy revealed gangrenous appendix. Histopathology results came back as extensive necrosis of the appendix with multiple viable Schistosomal ova. Stool analysis revealed no ova. The patient received praziquantel therapy and now he is in a good condition. Conclusion: Clinicians and pathologist should be aware of schistosomal appendicitis, particularly in endemic areas like Sudan. Highlights: Schistomiasis can have variable ways of clinical presentations especially in endemic countries. Acute appendicitis can be one of the clinical presentations of schistosoma. Clinicians and pathologists should be aware of this rare presentation of schistosoma.